EFFECT OF THE PEEL EXTRACTS FROM TWO CAMPOMANESIA (MYRTACEAE) SPECIES ON ALLIUM CEPA L. (AMARYLLIDACEAE) - Silva, Bruno Araújo; Castro, Thiago Luis Aguayo de; Viana, Lucilene Finoto; Mascarenhas Santos, Maria do Socorro; Cardoso, Claudia Andrea Lima (REVISTA DE AGRICULTURA NEOTROPICAL, 2022)
Species from the genus Campomanesia have been studied due to their biological activity and low toxicity. However, studies on the fruit peel of these species are scarce. In this context, the effects of ethanol extract from the fruit peel of Campomanesia sessiliflora (O. Berg) Mattos (CS) and Campomanesia guazumifolia (Cambess) O. Berg (CG) were evaluated concerning the effect on germination and meristem cells of roots of Allium cepa. The CG ethanolic extract showed flavonoid compounds higher than CS ethanolic extract. The CS extract showed no antioxidant activity. CS showed greater antiproliferative activity with reduced root size in A. cepa seeds. The two extracts did not induce mutagenicity and cell death at the studied concentration of 1 mg mL-1. Keywords: Germination, Allelopathy, Ethanolic extract.